PENGARUH PERKEMBANGAN ANAK TERHADAP POLA MAKAN : STUDI LITERATUR - erlinda, Erlinda (Jurnal Kesehatan, 2024)
This study aims to evaluate the influence of health on the development of toddlers in urban areas. Data was collected through a health and development survey for children under five, which involved measuring weight, height, nutritional status, and general health checks. The research results show that factors such as diet, home environment, access to health services, and sanitation practices significantly influence the health status of toddlers. These findings highlight the importance of interventions focused on improving the accessibility and quality of health services, as well as promoting healthy lifestyles and good sanitation in efforts to improve the health of children under five in urban areas. By understanding the factors that influence the health of children under five, it is hoped that more effective interventions can be designed to improve the well-being of young children.